Non-expert listeners show decreased heart rate and increased blood pressure (fear bradycardia) in response to atonal music - Proverbio, Alice M.; Manfrin, Luigi; Arcari, Laura A.; De Benedetto, Francesco; Gazzola, Martina; Guardamagna, Matteo; Lozano Nasi, Valentina; Zani, Alberto (Frontiers in Psychology, 2015)
Previous studies suggested that listening to different types of music may modulate differently psychological mood and physiological responses associated with the induced emotions. In this study the effect of listening to instrumental classical vs. atonal contemporary music was examined in a group of 50 non-expert listeners. The subjects’ heart rate and diastolic and systolic blood pressure values were measured while they listened to music of different style and emotional typologies. Pieces were selected by asking a group of composers and conservatory professors to suggest a list of the most emotional music pieces (from Renaissance to present time). A total of 214 suggestions from 20 respondents was received. Then it was asked them to identify which pieces best induced in the listener feelings of agitation, joy or pathos and the number of suggested pieces per style was computed. Atonal pieces were more frequently indicated as agitating, and tonal pieces as joyful. The presence/absence of tonality in a musical piece did not affect the affective dimension of pathos (being touching). Among the most frequently cited six pieces were selected that were comparable for structure and style, to represent each emotion and style. They were equally evaluated as unfamiliar by an independent group of 10 students of the same cohort) and were then used as stimuli for the experimental session in which autonomic parameters were recorded. Overall, listening to atonal music (independent of the pieces’ emotional characteristics) was associated with a reduced heart rate (fear bradycardia) and increased blood pressure (both diastolic and systolic), possibly reflecting an increase in alertness and attention, psychological tension, and anxiety. This evidence fits with the results of the aesthetical assessment showing how, overall, atonal music is perceived as more agitating and less joyful than tonal one.